Effects of an overnight high-carbohydrate meal on muscle glycogen after rapid weight loss in male collegiate wrestlers - Emi Kondo; Keisuke Shiose; Takuya Osawa; Keiko Motonaga; Akiko Kamei; Kohei Nakajima; Hiroyuki Sagayama; Takahiro Wada; Shigeki Nishiguchi; Hideyuki Takahashi (BMC, 2021)
Abstract Background Severe rapid weight loss (RWL) induces a decrease in muscle glycogen (mGly). Nevertheless, adequate carbohydrate intake after RWL has not been reported to optimize muscle glycogen following a weigh-in the evening until a wrestling tournament morning. The purpose of this study was to investigate the effect of an overnight high-carbohydrate recovery meal of 7.1 g kg−1 following RWL on mGly concentration. Methods Ten male elite wrestlers lost 6% of their body mass within 53 h and then subsequently ate three meals, within 5 h, containing total of 7.1 g kg−1 of carbohydrates. mGly was measured by 13C-magnetic resonance spectroscopy before (BL) and after RWL (R0) at 2 h (R2), 4 h (R4), and 13 h (R13) after initiating the meal. Body composition, muscle cross-sectional area, and blood and urine samples were collected at BL, R0, and R13. Results Body mass decreased by 4.6 ± 0.6 kg (p < 0.05) and did not recover to BL levels in R13 (− 1.7 ± 0.6 kg, p < 0.05). Likewise, mGly by 36.5% ± 10.0% (p < 0.05) and then did not reach BL levels by R13 (p < 0.05). Conclusion A high-carbohydrate meal of 7.1 g kg−1 after 6% RWL was not sufficient to recover mGly during a 13 h recovery phase. Participating in high-intensity wrestling matches with an mGly concentration below normal levels is maybe undesirable.